Impact of multi-busbar front grid patterns on the performance of industrial type c-Si solar cell. (1st April 2022) - Panda, T.; Sadhukhan, S.; Acharyya, S.; Banerjee, P; Nandi, A.; Bose, S.; Mondal, N.; Das, G.; Maity, S.; Chaudhuri, P.; Saha, H.
Highlights: Theoretical calculations (optimization) are carried out for the total front contact losses (viz. optical and electrical) of commercially available patterns solar cell. The levelized cost of energy (LCOE) due to Silver (Ag) paste has also been estimated for production of 10 MW power. The effect of increasing number of busbars on solar cell performance is analyzed here. The EM field distribution due to incident photon flux is also shown here using COMSOL Multiphysics simulation software. Abstract: Solar cell performance is highly dependent upon the front contact grid design for minimizing the power losses due to shading (optical loss) and for proper collection of the photo-generated charge carriers (electrical loss). In this paper, theoretical calculations (optimization) have been carried out for the total power losses (viz. optical and electrical) due to different front grid multi-busbar patterns similar to the ones currently used in industrial production. Busbar width and finger spacing, the two important design parameters of solar cell with standard busbar structure, are optimized for multi busbar systems. Role of interlinks between the fingers to reduce the power loss has also been studied. The effect of each optimized grid design on the component in the levelized cost of electricity (LCOE) due to Silver (Ag) requirement has been estimated for a 10 MW power system with a 25 years lifespan. The study of EM field distribution due to incident photon flux shows that increasing the number of busbars can generate carriers within the shaded areas under the busbars.